Cytogenetically Unrelated Clones in Acute Myeloid Leukemia Showing Different Responses to Chemotherapy - Kohei Kasahara; Masahiro Onozawa; Naohiro Miyashita; Emi Yokohata; Miho Yoshida; Minoru Kanaya; Mizuha Kosugi-Kanaya; Ryo Takemura; Shojiro Takahashi; Junichi Sugita; Akio Shigematsu; Mutsumi Takahata; et al. (Case Reports in Hematology)
We report a case of acute myeloid leukemia (AML) with two cytogenetically unrelated clones. The patient was a 45-year-old male who was diagnosed with acute monoblastic leukemia (AMoL). Initial G-band analysis showed 51,XY,+6,+8,inv(9)(p12q13)c,+11,+13,+19[12]/52,idem,+Y[8], but G-band analysis after induction therapy showed 45,XY,-7,inv(9)(p12q13)c[19]/46,XY,inv(9)(p12q13)c[1]. Retrospective FISH analysis revealed a cryptic monosomy 7 clone in the initial AML sample. The clone with multiple trisomies was eliminated after induction therapy and never recurred, but a clone with monosomy 7 was still detected in myelodysplastic marrow with a normal blast percentage. Both clones were successfully eliminated after related peripheral blood stem cell transplantation, but the patient died of relapsed AML with monosomy 7. We concluded that one clone was de novo AMoL with chromosome 6, 8, 11, 13, and 19 trisomy and that the other was acute myeloid leukemia with myelodysplasia-related changes　(AML-MRC) with chromosome 7 monosomy showing different responses to chemotherapy. Simultaneous onset of cytogenetically unrelated hematological malignancies that each have a different disease status is a rare phenomenon but is important to diagnose for a correct understanding of the disease status and for establishing an appropriate treatment strategy.